The Cauchy Problem for a Weakly Dissipative 2-Component Camassa-Holm System. (3rd February 2014) - Ming, Sen; Yang, Han; Wu, Yonghong
Abstract : The weakly dissipative 2-component Camassa-Holm system is considered. A local well-posedness for the system in Besov spaces is established by using the Littlewood-Paley theory and a priori estimates for the solutions of transport equation. The wave-breaking mechanisms and the exact blow-up rate of strong solutions to the system are presented. Moreover, a global existence result for strong solutions is derived.